PENGGUNAANMULTIMEDIA INTERAKTIF UNTUKMENINGKATKANKEMAMPUANMEMBACA AKSARA JAWA PADA SISWA KELAS 5 SDNEGERI BLIMBING 4 - Akbar Al Masjid; Ardian Arief (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The purpose of this study is to increase student motivation in learning and improving reading skills Javanese script for fifth grade students of Elementary School of Blimbing 4 Sukuharjo using multimedia interactive. This research is a classroom action research. This study uses a system of cycles, ranging from planning, action, observation and reflection than to next cycles. The subjects were the student of fifth grade of SD Negeri Blimbing 4. Data collection techniques used were observation, questionnaires, interview and discussion, review of documents, as well as tests. The technique of data validity checks using triangulation techniques and triangulation methods. For data analysis techniques used comparative descriptive and critical analysis. This research was conducted in two cycles.